PENGARUH PROFITABILITAS, PROPORSI DEWAN KOMISARIS, KOMITE AUDIT, DAN KARAKTER EKSEKUTIF TERHADAP PENGHINDARAN PAJAK (TAX AVOIDANCE) PADA PERUSAHAAN PROPERTY YANG TERDAFTAR DI BEI PERIODE 2010-2013 - Alfajri '; Zirman '; Sem Paulus (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2016)
This studyaimed toexamine the effect of profitability, independent commissioner board, audit committee and executive characteristics against tax avoidanceina property company listed on the Indonesia Stock Exchange (BEI) 2010-2013. The sample usedin this study is aproperty company that is listed on the Indonesia Stock Exchange basedon the selection criteria predefined sample. Sampling method used is purposive sampling and testing this hypothesis using multiple linear regression analysis. Proxy calculation of tax avoidancein the study using proxy Cash Effective Tax Rate (CETR) and the results of this study indicate that the independent variable Profitability proxy Return On Assets (ROA) and executive characteristics significantly affect the partial tax avoidance, but variable independent board and audit committee does not affect the partial tax avoidance, and the coefficient of determination (AdjustedR2) showed the value of 0.592. This suggests that the overall effectofthe independent variable profitability, independent board, audit committee and executive characteristics against tax avoidance amounted to only 59.2% while the remaining 40.8% influenced by other variables.Keyword : Tax Avoidance, Profitability, Independent Commissioner Board, Audit Committee and Executive Characteristics